2018
DOI: 10.1101/323394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Temporal-Resolution Dynamic PET Image Reconstruction Using A New Spatiotemporal Kernel Method

Abstract: Abstract-Current clinical dynamic PET has an effective temporal resolution of 5-10 seconds, which can be adequate for traditional compartmental modeling but is inadequate for exploiting the benefit of more advanced tracer kinetic modeling. There is a need to improve dynamic PET to allow fine temporal sampling of 1-2 seconds. However, reconstruction of these shorttime frames from tomographic data is extremely challenging as the count level of each frame is very low and high noise presents in both spatial and te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The reconstruction then becomes an optimisation problem in terms of ζ. This approach has been used in MMI : see [76,77,78] (PET with MRI), [79] (SPECT with PET), [80] (fluorescence molecular tomography with CT or MRI), [81] (DOT with CT), but also for MCMI : PET dynamic imaging using static images as guide [76] or temporal features derived from the raw data [82].…”
Section: (B)2 Kernel Methodsmentioning
confidence: 99%
“…The reconstruction then becomes an optimisation problem in terms of ζ. This approach has been used in MMI : see [76,77,78] (PET with MRI), [79] (SPECT with PET), [80] (fluorescence molecular tomography with CT or MRI), [81] (DOT with CT), but also for MCMI : PET dynamic imaging using static images as guide [76] or temporal features derived from the raw data [82].…”
Section: (B)2 Kernel Methodsmentioning
confidence: 99%
“…Nevertheless, the existing kernel methods only consider the spatial correlation. Wang (145) extended the spatial kernel method to the spatial-temporal domain, which can effectively reduce noise in the space and temporal domain for dynamic PET imaging.…”
Section: Image Reconstruction In Dynamic Imagingmentioning
confidence: 99%
“…Ellis et al proposed to use a weighted quadratic maximum a posteriori (MAP) method to reduce the noise of poorer‐quality PET images under the guidance of higher‐quality datasets 16,20 . In recent studies, 21 some researchers have also compared the MAP approach with the kernel method 22‐27 that has recently become popular. The comparison showed that for low‐count simulated datasets, the MAP‐related method performed poorly due to the inclusion of noisy PET information in the regularization term.…”
Section: Introductionmentioning
confidence: 99%